Breakthrough of the Positivism Paradigm in Judge’s Decisions as a Form of Reflection of Justice Values - Eviani, I Gusti Ayu; Windraswara, Juniardi; Jaedin; Abdurrahman, Alif; Mulyono, Galih Puji (Jurnal Cakrawala Hukum, 2024)
This research aims to analyze the Ferdy Sambo case through the lens of positivist thinking, which emphasizes facts and empirical evidence in the law enforcement process. This case became the public spotlight because it involved members of the police, the alleged motive for planning the loss of life was complex, and where there was a disparity in punishment between the decisions of the South Jakarta District Court and the DKI Jakarta High Court which imposed the death penalty. At the same time, the Supreme Court reduced the sentence to life imprisonment. This research uses normative legal research methods, emphasizing the study of legal norms or doctrine to uncover alternative interpretations and provide insight into specific issues. This research uses two methodologies: a legislative approach, which focuses on legal norms or laws, a conceptual approach, and a case approach, which examines the Supreme Court’s decision with the defendant Fredy Sambo. The results of this research discuss legal analysis by exploring the implications of the approach to the value of legal certainty and justice in the context of cases involving judicial power. This research also uses an approach from a positivist perspective. Through this approach, analysis is carried out on the investigation process, the evidence presented in court, how the legal system handles this case, and the sentence imposed by the judge.